Implementation of Class management Improving the Learning Process in Class VI Umar Bin Khattab SDIT Ummi Aida Medan, Medan Tembung District - Hikmatul Hidayah (Continuous Education: Journal of Science and Research, 2020)
In the context of the problem of improving the learning process, what can be done is to carry out classroom management. The purpose of this study is to find out how the implementation of class managementis carried out by teachers in the classroom in terms of improving the learning process at SDIT Ummi Aida Medan, Medan Tembung District. This research uses a qualitative approach with descriptive research type. Data collection techniques in this study using observation techniques (observation), and supported by interview observation techniques, and document study. The type of data used in this study is primary data by means of researchers making direct observations. Furthermore, all data are processed by qualitative data analysis stages, namely by reducing data, presenting data and drawing conclusions. This study resulted in four findings, namely: 1) Planning class managementincluding: teachers compiling educational calendars, prota and prosem, compiling syllabus, making lesson plans (RPP). 2) Implementation of class management includes: creating a classroom atmosphere, comfortable, safe and conducive and teachers are able to minimize obstacles in the teaching and learning process, approach students that cause learning obstacles, provide guidance and motivation to students to enthusiastically start learning, seating arrangements , the use of learning methods, and learning media that are adjusted to the learning material 3) Evaluation of Class Management includes: self-evaluation of educators to determine satisfaction in carrying out tasks as class dreamers, evaluation of learning outcomes of students.